A New Low-power, High-Q, Wide Tunable CMOS Active Inductor for RF Applications. Issue 2 (3rd March 2016) - Saad, Sehmi; Mhiri, Mongia; Hammadi, Aymen Ben; Besbes, Kamel
ABSTRACT: This paper presents a new topology for realizing a single-ended inductor employing a minimum number of passive components. The active inductor achieves a high quality factor of 895 over a frequency range of 1700 MHz. Its self-resonance frequency is 5.5 GHz. The achieved range of sweep for inductance ( L ) varies from 3.55 to 26 nH. The circuit draws 0.5 mA current from 1.0-V supply and occupies an effective active area of 22 × 27.5 µm 2, while the noise voltage is less than . The proposed inductor is designed and simulated in a 90-nm TSMC MS/RF CMOS process.